The effectiveness of the ASH Analog Experimenter as Electronic Learning Media for PIP Semarang Cadet - Andy Wahyu Hermanto; Sri Wahyuti; Nora Listantia (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Electronics is one of the courses in the Engineering study program. In this electronics course, cadets or students are given knowledge about electronic components and how to assemble electronic circuits. For this reason, in studying electronics, lecturers not only provide theoretical material, but also must be able to guide cadets in carrying out practicum in the laboratory. ASH Analog Experimentar is a learning media that can be used for practical learning of Electronics in the Laboratory. The purpose of this study was to determine the effectiveness of the ASH Analog Experimenter as an Electronic Learning Media for PIP Semarang Cadets. The research method used in this study is a qualitative method. Data obtained from the results of distributing questionnaires to cadets. The results of the respondents' responses will be analyzed and concluded. Secondary data obtained from library studies, observation and documentation. From the results of data analysis, there are several things that can be concluded: For the Level of suitability or relevance, 49% stated that it was very suitable, 51% said it was suitable, For the appearance or performance of the ASH Analog Experimenter media, 53% said it was very good, 41% said it was good, 5% said they were in doubtfully, 1% said it was not good, for the level of security or safety of the tool, 50% stated that it was very safe, 46% said it was safe, 4% said it was doubtfully. For the level of efficiency, 47% stated that they were very efficient, 52% said they were efficient, 1% said they were unsure, for the level of understanding, 35% stated that they understood very well, 59% said they understood, 6% said they doubtfully. Thus, in general, ASH Analog Experimenter is very effectively used for electronic learning media for PIP Semarang Cadets.